Pengujian Fungsional Website Customer Relation Ship Management Menggunakan Standar ISO/IEC 29119 - I Gusti Ngurah Nyoman Dharma Manuarsa; Niko Bilhaq Assidiqi; Chairul Anwar (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This research aims to test the functionality of the website-based Purchase Order Monitoring Application developed at PT. Dinamika Elektra Mandiri uses the ISO/IEC 29119 standard. The website that was tested is a system that is important in protecting customers and preventing them from switching to competitors or called Customer Relationship Management which is used to support the collection of customer data and the company's operational activities. The main problem that is the main reason is the lack of structured testing that refers to international standards, so potential functional errors are not systematically identified. The research method used is software testing based on the ISO/IEC 29119 standard. Research stages include test planning, test scenario design, test implementation, and evaluation of test results for system function success criteria. The test results show the function of the tested system according to the user's needs. The conclusion of this research shows that software testing based on the ISO/IEC 29119 standard is able to provide systematic and measurable testing results and help improve the quality of the tested website. Keywords : Web Based Applications, Customer Relationship Management, ISO/IEC 29119, Software Testing, Purchase Order, System Monitoring. Abstrak Penelitian ini bertujuan untuk menguji fungsionalitas Aplikasi Monitoring Purchase Order berbasis website yang dikembangkan pada PT. Dinamika Elektra Mandiri menggunakan standar ISO/IEC 29119.Website yang diuji merupakan sistem yang penting dalam menjaga pelanggan dan menghindari agar mereka tidak beralih kepesaing atau disebut Customer Relationship Management yang digunakan untuk mendukung pengeloaan data pelanggan dan aktivitas operasional perusahaan. Permasalahan utama yang menjadikan alasan utama yaitu belum adanya pengujian terstruktur yang mengacu pada standar internasional, sehingga potensi kesalahan fungsional tidak teridentifikasi secara sistemantis. Metode peneltian yang digunakan yaitu pengujian perangkat lunak berbasis standar ISO/IEC 29119 . Tahapan Penelitian meliputi perncaan pengujian, perancangan skenario uji, pelaksanaan pengujian, serta evaluasi hasil pengujian untuk kriteria keberhasilan fungsi sistem. Hasil pengujian menunjukkan fungsi sistem yang diuji sesuai dengan kebutuhan pengguna. Kesimpulan dari penilitian ini menunjukkan pengujian perangkat lunak berbasis standar ISO/IEC 29119 mampu memberikan hasi kerja pengujian yang sistematis dan terukur serta membantu meningkatkan kualitas pada website yang di uji. Kata Kunci : Aplikasi Berbasis Web, Customer Relationship Management, ISO/IEC 29119, Pengujian Perangkat Lunak, Purchase Order, Monitoring Sistem.